Job Satisfaction Mediates the Effect of EMR Implementation on Midwifery Care Quality - Ayu Hendrati Rahayu; Lusi Marlina; Rochmawati (Global Medical & Health Communication (GMHC), 2025)
Electronic medical record (EMR) implementation influences healthcare quality, but psychological mechanisms remain underexplored in midwifery contexts. This study examined EMR's effect on midwifery care quality with job satisfaction as a mediating variable. A cross-sectional study involved 450 midwives from healthcare facilities in DKI Jakarta, West Java, and Central Java from March to June 2025. Participants were selected through a multi-stage cluster sampling design with stratification by facility type. Data were collected using validated self-administered questionnaires measuring EMR implementation (30 items, α=0.952), job satisfaction (25 items, α=0.943), and care quality (35 items, α=0.923). All instruments demonstrated excellent psychometric properties with factor loadings ranging from 0.71 to 0.89 and average variance extracted values of 0.652 to 0.694. Structural equation modeling using SmartPLS 4.0 with bootstrapping (5,000 subsamples) and the Sobel test was used to analyze the direct and indirect relationships among variables. EMR implementation significantly affected care quality (β=0.689, t=12.352, p<0.001, R2=0.508) and job satisfaction (β=0.367, t=5.352, p<0.001, R2=0.135). Job satisfaction positively influenced care quality (β=0.060, t=2.757, p=0.028). Sobel test confirmed partial mediation (Z=2.450>1.96, p<0.05), indicating that job satisfaction mediates the relationship between EMR implementation and care quality. The total effect (c'=0.735) exceeded the direct effect (c=0.713), demonstrating that EMR influences care quality through both technological and psychological pathways. In conclusion, EMR implementation improves midwifery care quality through direct technological pathways and indirect psychological mechanisms, including job satisfaction, supporting holistic implementation strategies that consider human factors alongside technical aspects in maternal healthcare digitalization initiatives.